Analysis the dispersive nature of Love wave in fibre‐reinforced composite materials plate: A Green's function approach. (10th September 2022) - Kumar, Dharmendra; Kumhar, Raju; Kundu, Santimoy; Gupta, Shishir
Abstract : The research article mainly focuses on investigating the dispersive behaviour of Love waves influenced by an impulsive point source in a fibre‐reinforced magnetoelastic (FRME) plate placed on functionally graded fibre‐reinforced visco‐elastic (FGFRVE) semi‐infinite stratum. The materials of the considered structure have been assumed under the influence of magnetic field and functionally graded. The functionally graded in the lower semi‐infinite space is caused by consideration of quadratic variation in the shear moduli and mass density. Maxwell's equation and generalised Ohm's law have been employed to calculate the Laurentz force in the fibre‐reinforced magnetoelastic (FRME) plate. For solving the coupled field equations, three‐dimensional Green's function and Fourier transform are applied; consequently, the closed‐form of the Love wave's dispersion relation is obtained. The obtained dispersion curve is plotted and compared in the numerical results and discussions by taking the different magnitude of materials quantities such as reinforcement parameter, magnetoelastic coupling parameter, functionally graded parameter, and visco‐elastic parameter. In some particular cases, the deduced dispersion equation is found to be identical to the classical Love wave equation for uniform homogeneous isotropic cases, indicating that the assumed structures are valid. The obtained results from the entire study can be utilised to better understand the dispersive nature of Love wave propagation in the considered systems containing fibre‐reinforced, magnetoelastic, viscoelastic, and point sources.